2011
DOI: 10.1128/mcb.05659-11
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Grb14 Is an Endogenous Inhibitor of Retinal Protein Tyrosine Phosphatase 1B, and Light-Dependent Activation of Src Phosphorylates Grb14

Abstract: Growth factor receptor-bound protein 14 (Grb14) is an adapter protein implicated in receptor tyrosine kinase signaling. Grb14 ؊/؊ studies highlight both the positive and negative roles of Grb14 in receptor tyrosine kinase signaling in a tissue-specific manner. In this study, we made a novel finding that Grb14 inhibits the activity of PTP1B, the major negative regulator of insulin receptor (IR) signaling, in a phosphorylationregulated manner. Phosphorylation of Tyr-347 in the BPS domain of Grb14 is critical for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 42 publications
5
61
0
1
Order By: Relevance
“…Consistent with this idea, our laboratory previously reported a light-dependent activation of several oncogenic signaling proteins, including insulin receptor, non-receptor tyrosine kinases, phosphoinositide 3-kinase, and Akt in photoreceptor cells183037. We have observed no effect of light on the activation of oncogenic receptor and non-receptor tyrosine kinases in mouse retinas that are deficient in rhodopsin photobleaching303839, further establishing the role of photobleachable visual pigments in this process.…”
Section: Discussionsupporting
confidence: 65%
“…Consistent with this idea, our laboratory previously reported a light-dependent activation of several oncogenic signaling proteins, including insulin receptor, non-receptor tyrosine kinases, phosphoinositide 3-kinase, and Akt in photoreceptor cells183037. We have observed no effect of light on the activation of oncogenic receptor and non-receptor tyrosine kinases in mouse retinas that are deficient in rhodopsin photobleaching303839, further establishing the role of photobleachable visual pigments in this process.…”
Section: Discussionsupporting
confidence: 65%
“…We have recently demonstrated that phosphorylated Grb14 is a competitive inhibitor of the insulin receptor phosphatase, protein-tyrosine phosphatase 1B (8). It is tempting to speculate that Grb14 may regulate the phosphorylation or dephosphorylation of PDE itself or some other transduction protein, which then alters PDE function.…”
Section: Discussionmentioning
confidence: 99%
“…Grb14 undergoes tyrosine phosphorylation by light-activated non-receptor-tyrosine kinase Src, and phosphorylated Grb14 acts as a positive regulator of the insulin receptor (8). By competing for protein-tyrosine phosphatase 1B (PTP1B), a negative regulator of the insulin receptor (8), phosphorylated Grb14 enhances activation of the insulin receptor (9).…”
mentioning
confidence: 99%
“…The PTP1B dephosphorylates IR, and the un-phosphorylated form of Grb14 inactivates IR by direct binding to the catalytic loop of the IR; consequently, the IR becomes inactive [20, 21]. In light, the IR overcomes the inactivation by PTP1B and Grb14 through photobleaching of rhodopsin, which activates a non-receptor tyrosine kinase, Src [22, 23], that phosphorylates Grb14. The phosphorylated Grb14 acts a competitive inhibitor of PTP1B and inhibits its activity [22], and protects the IR from dephosphorylation [23].…”
Section: Introductionmentioning
confidence: 99%